Giving the Virus a "Realistic Feel": COVID-19 and the Rhetoric of Medical Models. (2nd July 2020) - Lazevnick, Ashley
Abstract : This article situates the digital model of SARS-CoV-2 within a longer history of imagining technologies that have given visual form to scientific phenomena. Using the Protein Data Bank of three-dimensional models, medical illustrators constructed a model of the protein-spiked virus. What does it mean to make something invisible to the naked eye tangible? What is the place of emotion, affect, and persuasion in this process? To answer these questions, this article compares the COVID-19 model with Niels Bohr's diagram of the atom and James Watson and Francis Crick's model of the DNA double-helix.